Developing Effective Procedures for Public Participation in Spatial Planning Regulation in Indonesia: Lesson Learned from Australia - Widiatedja, I Gusti Ngurah Parikesit; Ranawijaya, Ida Bagus Erwin; Purwani, Sagung Putri ME; Dwi Atmaja, Bima Kumara (Faculty of Law, Universitas Padjadjaran, 2023)
Public participation is a crucial aspect of spatial planning, serving to achieve sustainable development objectives. The Indonesian government has recognized this fact andincorporated public participation in its spatial planning lawsand regulations. However, procedures for involving the public have been criticized for lacking genuine participation, highlighting opportunities for public input only being offeredformally. Meanwhile, public participation is considered a significant component of spatial planning regulation in Australia, particularly in Victoria. The government has involved the public in various stages of the planning process, including creating a planning scheme, issuing planning permits, and completing planning agreements. Based on the established procedures under current Australian legislation, this study aims to provide a practical solution by examining and contrasting the role of public participation in spatial planning regulation between Indonesia and Australia. This study concluded that Indonesia might consider adopting Australia's strategy and setting up planning panels to regulate spatial planning. Planning agreements can also be advantageous, particularly for large-scale or mega projects that significantly negatively impact the environment and local communities. DOI: https://doi.org/10.22304/pjih.v10n3.a5